[n]cycloparaphenylenes with charges: cyclic conjugation at last - Casado-Cordón, Juan (My University, 2016)
Oligophenylenes (polyphenylenes) are constituted by an array of conjugated benzenes where inter-ring electron delocalization tends to extend over the whole chain (linear conjugation) being intrinsically limited, among other factors, by terminal effects. Alternatively, cyclic conjugation is envisaged as the unlimited free-boundary versionofconjugation which will impact the structure of molecules in rather unknown ways. The cyclic version of oligophenylenes, cycloparaphenylenes ([n]CPPs with n the number of phenyl rings) were first synthesized in 2008 by Beztozzi and Jasti.1 Today the whole [n]CPP series from [5]CPP to [18]CPP has been prepared. [n]CPPs represent ideal models to investigate new insights of the electronic structure of molecules and cyclic conjugation when electrons or charges circulate in a closed circuit without boundaries. Radical cations and dications of [n]CPP from n=5 to n=12 have been prepared and studied by Raman spectroscopy.2 Small [n]CPP dications own their stability to the closed-shell electronic configuration imposed by cyclic conjugation. However, in large [n]CPP dications cyclic conjugation is minimal and these divalent species form open-shell biradicals. The Raman spectra reflect the effect of cyclic conjugation in competition with cyclic strain and biradicaloid aromatic stabilization. Cyclic conjugation provokes the existence of a turning point or V-shape behavior of the frequencies of the G bands as a function of n. In this communication we will show the vibrational spectroscopic fingerprint of this rare form of conjugation. [1] R. Jasti, J. Bhattacharjee, J. B. Neaton, C. R. Bertozzi, “Synthesis, Characterization, and Theory of [9]-, [12]-, and [18]Cycloparaphenylene: Carbon Nanohoop Structures”, J. Am. Chem. Soc. 130 (2008), 17646–17647. [2] M. P. Alvarez, P. M. Burrezo, M. Kertesz, T. Iwamoto, S. Yamago, J. Xia, R. Jasti, J. T. L. Navarrete, M. Taravillo, V. G. Baonza, J. Casado, “Properties of Sizeable [n]CycloParaPhenylenes As Molecular Models of Single-Wall Carbon Nanotubes By Raman Spectroscopy: Structural and Electron-Transfer Responses Under Mechanical Stress”, Angew. Chem. Int. Ed. 53, (2014), 7033−7037.
[n]cycloparaphenylenes with charges
Keywords: Espectroscopía; Spectroscopy; Molecular materials